2014
DOI: 10.6026/97320630010196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sequence analysis of bacterial symbionts from the marine sponges Geodia cydonium and Ircinia muscarum

Abstract: Marine sponges (Porifera) live in a symbiotic relationship with microorganisms, primarily bacteria. Recently, several studies indicated that sponges are the most prolific source of biologically-active compounds produced by symbiotic microorganisms rather than by the sponges themselves. In the present study we characterized the bacterial symbionts from two Demospongiae, Ircinia muscarum and Geodia cydonium. We amplified 16S rRNA by PCR, using specific bacterial-primers. The phylogenetic analysis revealed the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…In this study, bacterial ascidian-derived strains from the genus Bacillus had the highest antimicrobial and antiproliferative activities, supporting the hypothesis that they might play a protective role in their hosts [75]. Bacillus strains are widely distributed in marine environments and are found to be associated with marine animals [76, 77]. They are culturable on many general-purpose media and have high proliferation rates and great adaptability [75].…”
Section: Discussionsupporting
confidence: 62%
“…In this study, bacterial ascidian-derived strains from the genus Bacillus had the highest antimicrobial and antiproliferative activities, supporting the hypothesis that they might play a protective role in their hosts [75]. Bacillus strains are widely distributed in marine environments and are found to be associated with marine animals [76, 77]. They are culturable on many general-purpose media and have high proliferation rates and great adaptability [75].…”
Section: Discussionsupporting
confidence: 62%
“…Sponges, due to the enormous diversity of associated microorganism communities, have always been considered an explicit source of pharmaceutical products. Our recent results showed that a diverse assemblage of bacteria resided in the marine sponge G. cydonium [ 27 ], including Pseudoalteromonas spp. that is reported to produce prodigiosin, a well-known tripyrrolic red pigment with immunosuppressive and anticancer activities, mainly in human breast cancer [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 1 0 carbon on the hexose sugar has an α linkage to the 1 carbon of the sphingosine base, and therefore these molecules highly resemble αGalCer in structure (Kawahara et al, 2002(Kawahara et al, , 2000. Because marine sponges harbor many bacteria that give rise to unusual metabolic products (Zuppa, Costantini, & Costantini, 2014); therefore, it is reasonable to propose that a bacteria associated with or colonizing the sponge A. mauritanius synthesized the first-discovered antigenic GSL. Representatives of this class of antigens are GSL-1 and GSL-1 0 .…”
Section: Glycosphingolipidsmentioning
confidence: 99%